Pro WF Windows Workflow in .NET 4 - Bukovics, Bruce; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
Windows Workflow Foundation (WF) is a revolutionary part of the .NET 4 Framework that allows you to orchestrate human and system interactions as a series of workflows that can be easily mapped, analyzed, adjusted, and implemented. As business problems become more complex, the need for workflow-based solutions has never been more evident. WF provides a simple and consistent way to model and implement complex problems. As a developer, you focus on developing the business logic for individual workflow tasks. The runtime handles the execution of those tasks after they have been composed into a workflow. Pro WF: Windows Workflow in .NET 4 provides you with the skills you need to incorporate WF in your applications, using a lively tutorial style with each example illustrated in C#. This book gets you up to speed with WF 4 quickly and comprehensively. Learn about WF 4$1 (Bs new designer, it$1 (Bs updated programming paradigm, and the completely new set of activities that can enable and extend your workflows. This book also includes detailed coverage of how to customize your workflows and access them in a variety of ways and situations so you can maximize the advantages of this technology.s
A Quick Tour of Windows Workflow Foundation -- Foundation Overview -- Activities -- Workflow Hosting -- Procedural Flow Control -- Collection-Related Activities -- Flowchart Modeling Style -- Host Communication -- Workflow Services -- Workflow Services Advanced Topics -- Workflow Persistence -- Customizing Workflow Persistence -- Transactions, Compensation, and Exception Handling -- Workflow Tracking -- Enhancing the Design Experience -- Advanced Custom Activities -- Hosting the Workflow Designer -- WF 3.x Interop and Migration.
Keywords: Computer science; Computer Science; Computer Science, general